Effect of the minority ions on the ICRF heating of fusion plasmas - Pavlenko, I.V.; Girka, I.O.; Leviga, B.I. (Вопросы атомной науки и техники, 2012)
Additional plasma heating, for example ICRF (Ion Cyclotron Range of Frequencies) heating, allows heating only a group of the fuel particles which will initiate the thermonuclear fusion reaction. But the ICRF heating scenarios are sensitive to the small fractions of the impurities, the fusion products and the minority ions. Therefore the optimization of the fraction ratio between the fuel ions and other ion components is required. It takes into consideration the effect of the ion components on the heating mechanism, the power interchange between the plasma components and the power loss channels from the confinement volume. The conditions of transferring from minority heating regime to the mode conversion one is studied for the reactor relevant D-T experiments.